(untitled) - Goldschmidt, Arthur (Boulder, Colorado, 2000)
Provides biographical sketches and source material for about 400 men and women who have played a major role in Egypt's national life. Entries range in length from half a page to two pages, and describe the contributions of politicians, writers, diplomats, religious leaders, and scholars, as well as founders of newspapers, department stores, theatrical troupes, and innovative techniques of visual representation. Earliest figures profiled are from the late 18th and early 19th centuries.
Keywords: Egypt,Egypt; History,Biography dictionaries,History,Biography dictionaries; 1517-1882,1798-